2022
DOI: 10.3390/foods11152256
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantification of Capsaicinoids and Phenolic Compounds in Two Types of Chili Olive Oils, Using HPLC/MS

Abstract: Chili olive oil is a popular addition to various foods in many countries. In a detailed study, the content of phenols and capsaicinoids in chili olive oil was determined using chili flakes and whole chilies. A total of 99.8% of the phenols in chili olive oil were secoiridoids, with elenolic acid, oleuropein aglycones, and ligostride aglycones being the most abundant. Chili olive oil with chili flakes contained higher levels of capsaicinoids (+21.6%) compared to whole chili olive oil. Capsaicin and dihydrocapsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The results of this study (Table 5) showed that parent and hybrid chilies contain polyphenol compounds and were grown in a controlled environment in a greenhouse. Polyphenol contents in peppers were been reported in other studies [14,38], which indicated that the potential for polyphenols in hybrids is more significant than in this study. It was reported in previous studies that there is a correlation between capsaicin and polyphenol content [37].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results of this study (Table 5) showed that parent and hybrid chilies contain polyphenol compounds and were grown in a controlled environment in a greenhouse. Polyphenol contents in peppers were been reported in other studies [14,38], which indicated that the potential for polyphenols in hybrids is more significant than in this study. It was reported in previous studies that there is a correlation between capsaicin and polyphenol content [37].…”
Section: Discussionsupporting
confidence: 61%
“…Chili has a major compound, namely, capsaicin, that makes it spicy [7]. Recent research reports that chili peppers have other functional compounds including: total phenolic content [11], carotenoids [12], terpenoids [13], total flavonoids [14], antioxidant activity [15], and α-glucosidase inhibitory (AGI) activities [16]. α-glucosidase inhibition has an important role in helping patients with type 2 diabetes mellitus [17].…”
Section: Introductionmentioning
confidence: 99%